Predictive value of cystatin C in people with suspected or established coronary artery disease: A meta-analysis. (August 2017) - Yang, Shaohui; Song, Luorui; Zhao, Lei; Dong, Pingshuan; Lai, Lihong; Wang, Honglei
Abstract: Background and aims: Circulating cystatin C has been recognized as an independent predictor of cardiovascular and all-cause mortality in the general population. We aimed to evaluate the prognostic value of baseline circulating cystatin C levels in people with suspected or established coronary artery disease (CAD) by conducting a meta-analysis. Methods: We searched Pubmed and Embase databases up to October 2016 for prospective observational studies investigating the predictive value of elevated circulating cystatin C levels in people with suspected or established CAD. Adverse vascular outcomes included all-cause mortality, cardiovascular mortality, or total adverse vascular events consisting of death, myocardial infarction, revascularization, stroke, and heart failure. Results: Ten studies involving participants with known or suspected CAD were included in this meta-analysis. When comparing the highest with the lowest cystatin C levels, the pooled hazard ratio (HR) was 2.27 (95% confidence interval [CI] 1.86–2.78) for all-cause mortality, 2.24 (95% CI 1.69–2.97) for cardiovascular mortality, and 1.87 (95% CI 1.57–2.24) for total adverse vascular events, respectively. Subgroup analysis results showed that this association was not influenced by follow-up duration, region, or CAD type. Conclusions: Elevated circulating cystatin C is independently associated with adverse vascular outcomes in people with suspected or established CAD in terms of all-cause mortality, cardiovascular mortality, and total adverse vascular events. This increased risk is probably independent of creatinine/estimated glomerular filtration rate. Highlights: Predictive value of cystatin C in people with suspected or established CAD is conflicting. Patients with the highest cystatin C levels had an 87% greater risk of total vascular events. Patients with the highest cystatin C levels had a 124% greater risk of cardiovascular mortality. Patients with the highest cystatin C levels had a 127% greater risk of all-cause mortality.